PROFESSIONAL EDUCATION IN SUSTAINABLE GASTRONOMY: RESULTS AND SOCIO-ENVIRONMENTAL IMPACTS - Pereira, Edson de Souza; Nascimento, Lucio Fabio Cassiano (Seven Editora, 2025)
This study analyzed the contribution of a professional education course in sustainable gastronomy to the promotion of conscious practices in the food sector. The research involved students and professionals from the sector, throughout theoretical and practical activities based on RDC No. 216/2004 and current health regulations. The results demonstrated significant progress in the adoption of good hygiene and sanitation practices, waste reduction, and more efficient use of inputs, in addition to strengthening critical awareness of food vulnerability. Participants began to identify themselves as promoters of change, replicating what they learned in their family and professional contexts. The analysis showed that the environmentally focused training strengthened students’ social commitment, generating significant transformations in daily habits. It is concluded that the training experience fostered the emergence of more reflective individuals committed to sustainability, expanding their actions toward integrated and responsible local development. DOI: https://doi.org/10.56238/sevened2025.029-094